The Relationship Between Work-Family Enrichment And Employee Engagement Among Employees In Selected Service Industry - Nor Liyana, Faizol Azmi (Universiti Malaysia Sarawak (UNIMAS), 2020)
The purpose of this study was to examine the relationship between work-family enrichment and employee engagement among employees in selected service industry. Questionnaire were administered to 98 employees in a selected service industry at Sibu, Sarawak. Pearson Correlation was used to test the hypotheses of the study. It can be confirmed that there is a significance relationship between work-family enrichment (affect) and employee engagement, there is a significance relationship between work-family enrichment (development) and employee engagement and there is a significance relationship between work-family enrichment (capital) and employee engagement. The findings of this study may provide useful information and body of knowledge for both practitioners and future researchers for the purpose of improving current policy on work-life enrichment.